E-Recruitment and Civic Organizational Management in Higher Education Institutions - Febi Nurcahya (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Digital transformation within campus-based civic organizations has become increasingly urgent as manual recruitment methods are no longer efficient nor capable of reaching diverse prospective members. This study aims to examine the implementation of e-recruitment, its effectiveness, and the managerial challenges that arise within digitalized cadre formation processes. The theoretical framework draws on Digital Management Theory, E-Recruitment Theory, and Organizational Capability Theory. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that e-recruitment enhances operational efficiency, expands inclusivity, and reduces selection bias, although technical issues, digital literacy gaps, and data security concerns remain. These results highlight that successful e-recruitment depends on technological readiness and adaptive organizational strategies. The study contributes empirical insights into the digitalization of non-formal organizations and provides practical recommendations for strengthening recruitment systems in higher education settings.